(untitled) (International journal of artificial intelligence, 2024)
The concept of "child" serves as a fundamental pillar in both Uzbek and English cultures, embodying a range of universal and linguacultural features that reflect societal values, beliefs, and practices surrounding childhood. As a pivotal stage of human development, childhood is not merely a biological phase but a complex construct shaped by cultural narratives and social norms. This exploration seeks to illuminate the rich tapestry of meanings associated with the "child" concept in both languages, highlighting how cultural contexts influence perceptions and expressions.